2009
DOI: 10.1007/s12648-009-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Dy3+ emission in M5(PO4)3F (M = Ca, Ba) phosphor

Abstract: : Ultrafine M 5 (PO 4 ) 3 F:Dy 3+ (M = Ca, Ba) phosphors were prepared via combustion process using metal nitrates as precursors. The formation of crystalline phosphate was confirmed by X-ray diffraction pattern. The PL excitation spectra show the excitation peaks observed at 250 to 400 nm due to f → f transition of Dy 3+ ion, which are useful for solid-state lighting purpose (mercury free excitation). The PL emission of Dy 3+ ion by 348 nm excitation gave an emission at 489 nm (blue), 582 nm (yellow) and 675 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The atomic percentage ratio of O concentration was slightly higher than the expected value, which was due to the environmental trace and combustible gases evolved during the reaction. 20 3.2. Photoluminescence Properties.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The atomic percentage ratio of O concentration was slightly higher than the expected value, which was due to the environmental trace and combustible gases evolved during the reaction. 20 3.2. Photoluminescence Properties.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The decrease in emission intensity at 1 mol% concentration of europium ion occurs as a result of concentration quenching. Shinde et al reported that the 300-400 nm is Hg-free excitation and it has characteristics of solid-state lighting phosphors (33). Consequently, the entire characteristics of Eu 2+ -doped SrCaP 2 O 7 reveal that, it is a promising blue emitting single-host phosphor for solid-state lighting devices (mercury-free excited lamp phosphor), which can be used in a color converter using UV light as the primary light source.…”
Section: Photoluminescence Properties Of Eu 2+ -Activated Srcap 2 Omentioning
confidence: 99%
“…For example, Ca 5 (PO 4 ) 3 F:Eu 2+ , Ca 5 (PO 4 ) 3 F:Tb 3+ , and other metal‐doped Ca 5 (PO 4 ) 3 F phosphors have been studied . However, there are few reports on the photoluminescence properties of Ca 5 (PO 4 ) 3 F:Dy 3+ phosphor until now, which can be used for fabricating w‐LEDs with white emission. As is known, Eu 3+ is widely used as a luminescence center in red‐emitting phosphors because of its 5 D 0 → 7 F 2 electron transition .…”
Section: Introductionmentioning
confidence: 99%